Effectiveness and feasibility of a motivational interviewing intake (MII) intervention for increasing client engagement in outpatient addiction treatment: an effectiveness-implementation hybrid design protocol - Margo C. Hurlocker; Theresa B. Moyers; Melissa Hatch; Geoffrey Curran; Barbara McCrady; Kamilla L. Venner; Katie Witkiewitz (Addiction Science & Clinical Practice, 2023)
Abstract Background Client discontinuation from outpatient addiction treatment programs is common, and the initial intake is the service delivery point with the highest attrition rate. Replacing the comprehensive intake assessment with a person-centered Motivational Interviewing (MI) intervention is a potential solution to address provider and client concerns about the disengaging, time-intensive nature of the typical initial intake. It remains unclear whether the use of an alternative to the standard intake at the initial visit can fit within typical organizational reporting requirements, whether it decreases attrition, and whether implementation of person-centered intake procedures within outpatient addiction treatment programs is feasible, acceptable, and can be sustained. Purpose To describe the methods and design of an effectiveness-implementation hybrid type 1 trial of a Motivational Interviewing at Intake (MII) intervention using the Consolidated Framework for Implementation Research (CFIR). Methods The study will determine the effectiveness of two intake conditions: (1) standard comprehensive intake assessment (intake-as-usual [IAU]), and (2) MII consisting of a person-centered discussion between provider and client about the client’s desire and intent to enter treatment. Although both interventions are focused on understanding client presenting complaints and needs for treatment, the delivery differs as the IAU uses a semi-structured assessment guide, while MII applies the theory of MI to have a conversation about treatment engagement. Adults seeking outpatient addiction treatment services will be randomly assigned to the MII condition (n = 75) or the IAU condition (n = 75). Primary outcomes will be client engagement (i.e., treatment entry, attendance, and completion) obtained from the electronic medical record. Secondary outcomes (client motivation and therapeutic alliance) will be putative mechanisms of client engagement assessed immediately before and after the intake. The trial also will explore determinants of effective, sustainable implementation using assessments of organizational readiness and capacity to change, as well as interviews on MII implementation feasibility. Conclusion This trial of an MII intervention will investigate the feasibility of a motivational intervention as an initial contact with substance use treatment-seeking clients as well as indicators of intervention effectiveness within the systems where it is employed. Trial registration Clinicaltrials.gov identifier: NCT05489068